Meningkatkan Kemampuan Menulis Siswa dalam Asking and Giving for Opinion dengan Menggunakan Teknik Make A Match, Sebuah Studi Kasus Kelas XI MIPA 2 SMA N 11 Semarang pada Tahun Akademik 2018/2019 - Khanurul Jannah (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2019)
Low of students’ writing ability and monotonous learning technique made the students less interested in the learning process. Based on the causes, the objectives of this research are: (1) To find out the improvement students’ ability in writing asking and giving for opinion. (2) To prove the effectiveness students’ ability in writing asking and giving for opinion by using Make a Match technique. This research was conducted two cycles. Each cycle consisted of planning, action, observation, and reflection. Data was collected with tests and non-test techniques. The subject of this research was XI MIPA 2 of 11 SHS Semarang. This research was conducted in the odd semester in academic year of 2018/2019. The result obtained the mean of students’ score in the first cycle was 78, the percentage completeness of students’ score was 75%. The mean of students’ score in the second cycle was 82, the percentage completeness of students’ score was 81%. Students’ score in each cycle have increased, with an increase in learning outcomes of 6%. Based on the results of the research, it can be concluded that the use of Make a Match technique improve students’ writing ability in asking and giving for opinion of XI MIPA 2 Class of 11 Senior High School Semarang. Beside that, the use of Make a Match technique could make students more active and created “fun” learning environment. Therefore, English teacher is recommended to use Make a Match technique in learning English to improve students’ writing ability.